Технологiя виготовлення керамiчних полив'яних писанок за археологiчними матерiалами Києва - Сушко, А.О. (Археологія, 2020)
Висвітлюються питання технології виготовлення керамічних полив’яних писанок на основі матеріалів, які були
виявлені на території міста Києва. Одним с ярчайших проявлений древнерусского керамического искусства были поливные писанки. Несмотря на
это, ныне еще существуют белые пятна в изучении этой категории археологического материала. Это касается
технологических аспектов. Изготавливали эти поделки с обычной гончарной глины ленточным способом. Их
формировали полыми, и во внутренний части они содержали маленький керамический шарик. После формовки
их обжигали, потом покрывали прозрачной поливой, которая служила фоном. В большинстве случаев использовалась полива зеленого и бурого цветов. Далее при помощи специального трубчатого инструмента наносили
роспись поливой другого цвета, как правило, желтого и зеленого, и изделие снова разогревали в печи для заглаживания поверхности. Росписи не отличались разнообразием. Существовало три основных типа узора: обычные
полосы, которые опоясывают изделие несколько раз, бессистемные, размещенные вдоль и поперек, а также
фигурные скобки, которые были наиболее характерным орнаментом.
Так подробный анализ небольшого количества материала позволил раскрыть технологию изготовления писанок. Glazed painted eggs were one of the most vivid manifestations of Ancient Rus’ ceramic art. Nevertheless, today there are
still unsolved problems in study of this category of archaeological material. It concerns technological aspects. These articles
were made of ordinary pottery loam in a band way. They were formed hollow and contained a small ceramic ball in the inner
part. After the molding they were fired, then covered with transparent glaze, which served as a background. In most cases
green and fulvous glaze was used. Then, by using a special tubular instrument the painting was made with glaze of another
colour, usually yellow and green, and the item was heated up again in the kiln in order to smooth the surface. Paintings
were not multifarious. There were three main types of designs: ordinary stripes, which surrounded the item several times;
unsystematic stripes that were put lengthwise and athwart; and also braces, which were the most common ornament.
The question of theAncient Rus’ glaze,which covered the glazed painted eggs,wasraised in the 1960-ies by T. Makarova.
However, today, on the basis of our collection and in the context of significant changes in the field of science, we have
succeeded in clarifying and extending the known facts. The Nanomedtech Electron Microscopy Laboratory with the help
of a Tescan Mira 3 LMU scanning microscope and the Gatan Pecs 682 precision etching and coating system was kindly
performed with spectral analysis.
Spectral analysis confirmed that Ancient Rus’ glaze had a lead-silica composition with a high content of tin. Brown
colour was obtained by iron oxide, yellow by lead, green by copper. A general glaze formula was developed, which should
consist essentially of Pb and Si oxide. On the example of two samples that have the same yellow colour, the difference in the
quantitative composition of the components and their percentage can be seen that, by-turn, confirms the view of the relative
dimensions of component measurement. The analysis of a small amount of material allowed describing the technology of
painted eggs manufacturing.